A New Supramolecular Assembly Obtained by Reaction Between Thiosaccharin and Pyridine - Piro, Oscar Enrique (2008)
The crystal structure of pyridinium thiosaccharinate thiosaccharin, [HNC5H5]+ [(tsac)(Htsac)]− (Htsac = C7H5NO2S2, the thiosaccharin molecule), was determined by single-crystal X-ray diffraction. Both, the thiosaccharinate anion, the corresponding neutral molecule and the pyridinium cation are nearly planar and arranged in the solid state in an almost parallel fashion, hence giving rise to a layered supramolecular structure. The anion shows small but significant modifications in the bonding of the thioamide group as compared with the neutral molecule. The crystal is further stabilized by an extensive H-bonding network. The FTIR spectrum of the compound is briefly commented.